2016
DOI: 10.1002/adfm.201504722
|View full text |Cite
|
Sign up to set email alerts
|

Charge‐Carrier Density Independent Mobility in Amorphous Fluorene‐Triarylamine Copolymers

Abstract: 3720 wileyonlinelibrary.com (OPVs), and organic fi eld-effect transistors (OFETs). A crucial parameter in the development of these technologies is the OSC charge-carrier mobility, and how it is related to the different OSC materials, processing, device architectures, and device operating conditions. Many semiconducting polymers and small molecules are amorphous, and such disorder in the physical morphology is expected to refl ect itself in disorder of the energy levels of the hole and electron transport states… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 63 publications
4
23
0
Order By: Relevance
“…For such materials, our proposed model here would be a better choice to extract the mobility for spatially disordered organic materials as we have shown that the traditional thickness scaling is not valid anymore. By applying our model with field-dependent mobility, we are able to reproduce the experimental results of SCLC transport in PPV derivative based device without using the carrier-density dependent mobility [1], agreeable with a recent report for amorphous polymers [3].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…For such materials, our proposed model here would be a better choice to extract the mobility for spatially disordered organic materials as we have shown that the traditional thickness scaling is not valid anymore. By applying our model with field-dependent mobility, we are able to reproduce the experimental results of SCLC transport in PPV derivative based device without using the carrier-density dependent mobility [1], agreeable with a recent report for amorphous polymers [3].…”
Section: Discussionsupporting
confidence: 89%
“…We first analyze various experimental results to study the thickness (or L) dependence to show that the traditional L scalings from the traditional models are not valid for spatially disordered semiconducting materials. By using our proposed models, we are able to reproduce the experimental currentvoltage measurements in [1] without using the carrier-density dependent model, and thus solving the issues raised by recent paper [3].…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…For organic semiconductors, field-dependent [12][13][14][15] and density-dependent mobility SCLC models 16,17 are commonly employed to characterize the SCLC carried by the holes. Similarly, SCLC of electrons was found to be universally described by a trap model with Gaussian energy distribution in a large class of organic semiconductors 18,19 .…”
Section: Introductionmentioning
confidence: 99%